HADITH STUDY OF MEDIA LITERACY SKILLS IN ISLAMIC EDUCATION - Sukawati Sukawati (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This research focuses on the literacy skills needed to understand hadith, especially the Islamic religious education program at STAI IBNU RUSYD Kotabumi. This study aims to evaluate students' literacy skills in deepening their understanding of the science of hadith and to measure how ready they are to apply what they have learned in society. The research method uses quantitative description. The data collection technique used a questionnaire with a Likert scale in the form of Google which was distributed to 150 respondents. The results of the study show that students generally have an interest of 63% in studying hadith. However, these results are not high enough. Therefore, it is very important to motivate students and use interesting teaching strategies to arouse their interest. Media literacy level with an average of 70% is in the high category. They are generally successful in using the media as a source of independent learning. They have practiced one aspect of the media literacy paradigm, namely determining needs before starting a search. In terms of the literature they choose to obtain information from, they prefer fast access, especially the internet. While printed books have relatively few enthusiasts. So a good understanding and education are needed on how to access valid information through various relevant information media.